Estudo de altas pressões do cristal de DL-ácido glutâmico monohidratado - VICTOR, Francisco Marcelo Sousa (2017)
In this work, DL-glutamic acid monohydrate crystals (DLAGM) were grown by the technique of slow evaporation of the solvent. Initially the crystal was characterized by Xray diffraction using the powder method and its structural parameters adjusted by the Rietveld method, and thus, its orthorhombic crystal structure of space group Pbca (D2h), with eight molecules per unit cell. Raman scattering measurements were performed and the vibrational normal modes of DLAGM crystal were tentatively assigned using, mainly, glutamic acid polymorph crystals. The DLAGM crystal was studied by Raman spectroscopy under conditions of high hydrostatic pressures up to 6.9 GPa, as well as by X-ray diffraction in the range of 3.0-15.0 GPa. Changes in the lattice modes show that the crystal undergoes a phase transition in the pressure range of 5.1-5.7 GPa characterized by the disappearance and splitting of bands as well as the discontinuity in the slope dω/dP of these vibrational modes, modifications in vibrational internal modes (NH3 +, CO2-, H2O) and appearance of new bands. In addition, decompression at ambient pressure shows that the phase transition is reversible. For pressure XRD measurements, a phase transition was observed in the same pressure range as in the Raman experiment (5.0-5.8 GPa), characterized mainly by the appearance of new peaks at 5.8 GPa. Comparing such behaviora with those of L-glutamic hydrochloric, α-glutamic and β-glutamic acids, a great stability is observed for DL-glutamic monohydrate.